Drugs: a school-based prevention programme (Journal of Parents and Teachers, 2026)
The study examines both the psychological and social causes underlying substance abuse. It also proposes various preventative measures to be implemented through schools and families.
Keywords: Preventative education; self-esteem; risk factors; school environmen; communication with families